Toxicity, physiological response, and biosorption mechanism of Dunaliella salina to copper, lead, and cadmium - Gao, Mingze; Ling, Na; Tian, Haiyan; Guo, Chunqiu; Wang, Qiyao (Frontiers in Microbiology, 2024)
Heavy metal pollution has become a global problem, which urgently needed to be solved owing to its severe threat to water ecosystems and human health. Thus, the exploration and development of a simple, cost-effective and environmental-friendly technique to remove metal elements from contaminated water is of great importance.Algae are a kind of photosynthetic autotroph and the primary producer in water. This paper aims to investigate the effects of heavy metals (copper, lead and cadmium) on the growth, biomolecules accumulation, metabolic responses and antioxidant response of Dunaliella salina. Moreover, the bioremediation capacity and adsorption mechanism of D. salina involved in metal ions removal were explored as well. The results revealed the growth of D. salina cells was significantly inhibited and the contents of intracellular photosynthetic pigments, polysaccharides and proteins were 2 obviously reduced under different concentrations of Cu 2+ , Pb 2+ and Cd 2+ , and the EC50 values were 18.14 mg/L, 160.37 mg/L and 3.32 mg/L at 72 h, respectively. Besides, the activities of antioxidant enzyme SOD and CAT in D. salina first increased, and then descended with increasing concentration of three metal ions, while MDA contents elevated continuously. Moreover, D. salina exhibited an excellent removal efficacy on three heavy metals. The Box-Behnken design (BBD) in response surface methodology (RSM) revealed that the maximal removal rates for Cu 2+ , Pb 2+ , and Cd 2+ were 88.9%, 87.2% and 72.9%, respectively under optimal adsorption conditions of pH 5-6, temperature 20-30℃, and adsorption time 6 h. Both surface biosorption and intracellular bioaccumulation mechanisms are involved in metal ions removal of D. salina. FTIR spectrum exhibited the main functional groups including carboxyl (-COOH), hydroxyl (-OH), amino (-NH2), phosphate (-P=O) and sulfate (-S=O) are closely associated with the biosorption or removal of heavy metals ions. To sum up, attributing to the brilliant biosorption capacity, Dunaliella salina may be developed to be an excellent adsorbent for heavy metals.